Norms establishment of the Diagnosis and Recommendation Integrated System (DRIS) for nutritional diagnosis of sugarcane - Reis Junior, Roberto dos Anjos; Monnerat, Pedro Henrique (Pesquisa Agropecuaria Brasileira, 2003)
The objectives of this study were to establish DRIS norms for sugarcane crop, to compare mean yield, foliar nutrient contents and variance of nutrient ratios of low- and high-yielding groups and to compare mean values of nutrient ratios selected as the DRIS norms of low- and high-yielding groups. Leaf samples (analyzed for N, P, K, Ca, Mg, S, Cu, Mn and Zn contents) and respective yields were collected in 126 commercial sugarcane fields in Rio de Janeiro State, Brazil and used to establish DRIS norms for sugarcane. Nearly all nutrient ratios selected as DRIS norms (77.8%) showed statistical differences between mean values of the low- and high-yielding groups. These different nutritional balances between the low- and high-yielding groups indicate that the DRIS norms developed in this paper are reliable. The DRIS norms for micronutrients with high S²l /S²h ratio and low coefficient of variation found can provide more security to evaluate the micronutrient status of sugarcane.